Assessment of the Archaeological Potential of Prehistoric Settlement Areas along the Lake Shores and Wetlands of Carinthia, Southern Austria - Ries, Marie-Claire (Rzeszów University Press, 2025)
The lake district of Carinthia’s Klagenfurt Basin in southern Austria offers remarkable potential for advancing interdisciplinary research on prehistoric settlement landscapes. Although Austria’s first pile-dwelling site was discovered in 1864 at Lake Keutschacher See today part of the UNESCO World Heritage property “Prehistoric Pile Dwellings around the Alps” – systematic archaeological surveys of Carinthia’s more than 1,000 lakes and wetlands have remained scarce. This paper presents a pilot project addressing this long-standing research gap by developing a new anchor point for the identification, documentation, and evaluation of submerged lakeside archaeological heritage and their general archaeological setting. Combining archival and literature studies with underwater field surveys, sediment coring, and laboratory analyses, the project provides an updated inventory of archaeological structures belonging to the chronological frame of the 5th to 3rd millennia BC. Activities conducted between 2021 and 2024 in collaboration with local museums, municipalities, students, and volunteers have provided new insights into settlement dynamics, technological innovation, and human–environment interactions during the Neolithic and Copper Age. The Kapuzinerinsel pile-dwelling site in Lake Wörthersee serves as an example of a new discovery demonstrating how targeted potential assessments can bridge persistent gaps in Austria’s archaeological record and contribute to improved local heritage protection as well as reinforce connections to neighbouring regions. Beyond generating new data, the study underscores the broader significance of the Alpe-Adria lakescapes as an important inner-Alpine corridor linking the Italian Peninsula, Southeastern Europe (the Balkans), and the northwestern circum-Alpine lake-dwelling regions. By integrating cultural and natural data, this research promotes sustainable and interdisciplinary approaches that position southern Austria within the wider European archaeological discourse and establish a foundation for future research and management strategies. The project additionally provides new absolute radiocarbon dates that contribute to a better understanding of Carinthia’s prehistory.
Keywords: prehistoric pile-dwellings; Eneolithic; Copper Age; Austrian archaeology; underwater archaeology